Study on the Path of Cultivating and Enhancing National Maritime Awareness Under the Threshold of the Great Power Game - WANG Fuxin; GE Yuxuan (Haiyang Kaifa yu guanli)
The essence of great power game lies in the conflict and game between major powers. In the current context, the game in the maritime domain extends beyond military and security aspects to encompass various fields such as maritime economy, maritime politics, maritime culture, and maritime ecology. Maritime consciousness, as a crucial factor of maritime soft power, holds significant implications for China to enhance its economic competitiveness, develop and safeguard maritime rights and interests, increase its influence in maritime culture, and promote sustainable maritime development. Therefore, it is imperative to cultivate and elevate the national maritime consciousness as a necessary response to great power game. However, compared to other maritime powers, China still faces challenges such as a lack of public participation in maritime economic activities, insufficient attention to maritime politics, limited understanding of maritime culture, and inadequate appreciation for the importance of the marine environment. To address these issues, efforts must be made to foster and enhance the national consciousness of maritime economy, maritime politics, maritime culture, and maritime ecology. By doing so, China can enhance its maritime hard power and soft power in economic, political, cultural, and ecological aspects, accelerate the construction of a maritime power, help realize the modernization of China, and effectively cope with the challenges brought by great power game.